Strategi Pemasaran Dan Branding Bagi Produk Oeh-Oleh Dalam Era Pariwisata Berkelanjutan - Fiona R. H; Annisa Prastika Qur’ani K.; Almira K Lahiya; Kusmiatun Khoiriyah; Nuraisyah Nuraisyah; Syarif Permana Salingkat; Gita Farista (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
. Batu is a city located in the province of East Java, Indonesia. It is well-known among many people for its cool climate and natural beauty, making it a popular tourist destination. The tourism sector encourages every business actor to develop marketing strategies that not only focus on financial gains but also consider environmental and social aspects. Souvenir products from Batu contribute significantly to the value of the tourism chain with their crucial role in strengthening destination identity, enhancing visitor experience, and supporting the local economy. This study aims to analyze the marketing and branding strategies implemented by souvenir businesses in the tourist city of Batu in order to respond to sustainable tourism developments. Batu City has very high potential in the micro, small, and medium enterprise sector, especially in specialty food products. However, with increasing competition, businesses are required to innovate in their marketing methods and strengthen their brand identity. The method used in this study is descriptive qualitative, involving literature review and analysis of phenomena in the field. The results of this study indicate that the use of digital marketing strategies, product innovation, environmentally friendly packaging, and brand narrative creation are important factors for competing in the era of sustainable tourism.